Any and its ‘free choice’ - van der Auwera, Johan (Kalbotyra, 2024)
Since Ladusaw (1979) the term ‘free choice indefinite’ is the generally accepted term for the meaning of any in primarily modal and generic sentences, such as Any owl hunts mice, but not for what is generally called the ‘polarity-sensitive’ or ‘negative polarity’ meaning, as in Did you take any? At least part of the inspiration for Ladusaw was Vendler (1967), but Vendler took a notion of ‘freedom of choice’ to characterize all uses of any. This paper has three goals: (i) to offer a critical survey, updating earlier ones by Horn (2000a, 2000b, 2005) of the question whether English any has one meaning – a univocal account – or two – an ambiguist account, with the two alleged meanings involving negative polarity, on the one hand, and free choice, on the other hand; (ii) to confirm, in agreement with much current work, that Vendler (1967) was right, and to suggest, in disagreement with most if not all current work, to make terminology reflect the insight and no longer restrict the term ‘free choice’ to just a few of the meanings of any; and (iii) to offer a new univocal approach of any, hypothesizing its meaning to contain the components ‘existence’ and ‘free choice’, and using the notion of ‘at-issueness’.